Fintech in the time of COVID−19: Technological adoption during crises - Fu, Jonathan; Mishra, Mrinal (Journal of Financial Intermediation, 2022)
We document the effects of the COVID−19 pandemic on digital finance and fintech adoption. Drawing on mobile application data from a globally representative sample, we find that the spread of COVID− 19 and related government lockdowns led to a sizeable increase in the rate of finance app downloads. We then analyze factors that may have driven this effect on the demand−side and better understand the “winners” from this digital acceleration on the supply−side. Our overall results suggest that traditional incumbents saw the largest growth in their digital offerings during the initial period, but that “BigTech” companies and newer fintech providers ultimately outperformed them over time. Finally, we drill−down further on the adoption of fintech apps pertaining to both the asset and liability side of the traditional bank balance sheet, to explore the implications that the accelerated trends in digitization may have for the future landscape of financial intermediation.